Assessing Public Awareness and Perception of Teledermatology Via Survey - Nihal Altunisik; Şule Gençoğlu; Dursun Türkmen; Serpil Şener (Mattioli1885, 2024)
Introduction: Teledermatology represents an alternative medical approach allowing for the remote assessment of a patient's clinical information without the need for face-to-face consultations. Objective: This study aims to gauge the public's awareness and perception of teledermatology. Methods: This research employed a cross-sectional observational design. Data collection was executed using an online survey. Sociodemographic attributes of all participants, such as age, gender, and occupation, were recorded. The survey, designed using Google Forms, comprised two sections: demographic information (5 questions) and queries related to teledermatology (10 questions). Questions and options in the survey were reviewed and revised by two dermatologists to eliminate potential misunderstandings, grammar, and other errors. Power analysis indicated a requirement of a minimum of 527 participants, given a 0.05 margin of error, 98% confidence level, and 0.50 response distribution. Results: A total of 873 individuals completed the survey- 47.7% were male and 52.3% were female. Students made up 48.1% of the participants, while 22.6% were civil servants. The Marmara Region had the highest participation rate at 47.7%. Remarkably, 41.9% of participants were unfamiliar with the term "teledermatology." However, 57.2% expressed a preference for consultations via teledermatology. Furthermore, 63.7% mentioned facing challenges when attempting to communicate with dermatologists for skin-related concerns. A notable 71.6% supported the formal implementation of teledermatology in our country. Conclusion: Our survey highlighted a limited awareness of teledermatology among participants, yet a majority showed a preference for teledermatology consultations. For a comprehensive understanding of public knowledge and perception towards teledermatology, more extensive, multicentric studies are necessary.